Surgery for Gastric Adenocarcinoma with Hospital Stay: A Prospective Study - Avinash Rinait1 , Yashwant R. Lamture2 , Pulavarty Prateek3 , Dilip Gode4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: With the new changing lifestyles and the control if infectious diseases, cancer is soon emergingto be one of the leading causes of deaths in developing countries like India. Surgical procedure showsimprovement in survival period for a patient at stage II and III after correcting the nutritional status of thepatients. There is a decline in post-operative complication with patients who underwent surgery. Hence thisstudy was undertaken to study the curative and palliative surgeries in the patients of gastric adenocarcinomaand their hospital stay.Methodology: This was a prospective study in which 50 of gastric adenocarcinoma patients who wereadmitted in the surgery department at Datta Meghe Medical College, Shalinitai Meghe Hospital and ResearchCentre, Nagpur in collaboration with Jawaharlal Nehru Medical College, Datta Meghe Institute of MedicalSciences, Sawangi Meghe, Wardha, Maharashtra were studied.Results: Majority of patients presented with Stage II (88%) while 12% presented with stage III. 82% patientsunderwent curative surgeries while 18% underwent palliative surgeries. The duration of hospital stays forGastric Adenocarcinoma surgery for Stage II ranges from 6-8 days (median 7 days) whereas for Stage IIIit is 7-8 days (median 7.5 day). A total of 50 patients who underwent surgery for histologically provengastric adenocarcinoma. Out of 50 patients a majority i.e. 88% presented in stage II while 12% presented instage III.Conclusion: On the basis of our observations we concluded that the patients presenting earlier in stage IIundergo curative surgeries most often and mean hospital stay post-surgery around a week.